Early pregnancy loss in patients with polycystic ovary syndrome after IVM versus standard ovarian stimulation for IVF/ICSI. Issue 12 (7th October 2020) - Mackens, S; Mostinckx, L; Drakopoulos, P; Segers, I; Santos-Ribeiro, S; Popovic-Todorovic, B; Tournaye, H; Blockeel, C; De Vos, M
Abstract: STUDY QUESTION: Is the incidence of early pregnancy loss (EPL) in patients with polycystic ovary syndrome (PCOS) higher after IVM of oocytes than after ovarian stimulation (OS) for IVF/ICSI? SUMMARY ANSWER: Women with PCOS who are pregnant after fresh embryo transfer have a higher probability of EPL following IVM, but after frozen embryo transfer (FET), no significant difference in the incidence of EPL was observed following IVM compared to OS. WHAT IS KNOWN ALREADY: There is conflicting evidence in the current literature with regard to the risk of EPL after IVM of oocytes when compared with OS. Because of the limited sample size in previous studies, the use of different IVM systems and the possible bias introduced by patient characteristics and treatment type, firm conclusions cannot be drawn. STUDY DESIGN, SIZE, DURATION: This was a retrospective cohort study evaluating 800 women, with a diagnosis of infertility and PCOS as defined by Rotterdam criteria, who had a first positive pregnancy test after fresh or FET following IVM or OS between January 2010 and December 2017 in a tertiary care academic medical centre. PARTICIPANTS/MATERIALS, SETTING, METHODS: Pregnancies after non-hCG triggered IVM following a short course of highly purified human menopausal gonadotropin were compared with those after conventional OS. The primary outcome was EPL, defined as a spontaneous pregnancy loss before 10 weeks of gestation. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 329 patients with a positive pregnancy test after IVM and 471 patients with a positive pregnancy test after OS were included. Women who were pregnant after IVM were younger (28.6 ± 3.4 years vs 29.3 ± 3.6 years, P  = 0.005) and had higher serum anti-Mullerian hormone levels (11.5 ± 8.1 ng/ml vs 7.2 ± 4.1 ng/ml, P  < 0.001) compared to those who were pregnant after OS. The distribution of PCOS phenotypes was significantly different among women in the IVM group compared to those in the OS group and women who were pregnant after OS had previously suffered EPL more often (28% vs 17.6%, P  = 0.003). EPL was significantly higher after fresh embryo transfer following IVM compared to OS (57/122 (46.7%) vs 53/305 (17.4%), P  < 0.001), while the results were comparable after FET (63/207 (30.4%) vs 60/166 (36.1%), respectively, P  = 0.24). In the multivariate logistic regression analysis evaluating fresh embryo transfer cycles, IVM was the only independent factor (adjusted odds ratio (aOR) 4.24, 95% CI 2.44–7.37, P  < 0.001)) significantly associated with increased odds of EPL. On the other hand, when the same model was applied to FET cycles, the type of treatment (IVM vs OS) was not significantly associated with EPL (aOR 0.73, 95% CI 0.43–1.25, P  = 0.25). LIMITATIONS, REASONS FOR CAUTION: The current data are limited by the retrospective nature of the study and the potential of bias due to unmeasured confounders. WIDER IMPLICATIONS OF THE FINDINGS: The increased risk of EPL after fresh embryo transfer following IVM may point towards inadequate endometrial development in IVM cycles. Adopting a freeze-all strategy after IVM seems more appropriate. Future studies are needed to ascertain the underlying cause of this observation. STUDY FUNDING/COMPETING INTEREST(S): The Clinical IVM research has been supported by research grants from Cook Medical and Besins Healthcare. All authors declared no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.